2001
DOI: 10.1007/s004080000060
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Recombinant Human DNase on α1-Proteinase Inhibitor Function: An Experimental Approach to the Combined Clinical Use of rhDNase and α1-PI in CF Patients

Abstract: Chronic inflammation in cystic fibrosis (CF) airways leads to high concentrations of deoxyribonucleic acid (DNA) and neutrophil elastase (NE). Both play a major role in CF lung pathophysiology and are aims of new therapeutic approaches: rhDNase degrades highly viscosic DNA and alpha1-proteinase inhibitor (alpha1-PI) inhibits NE activity and thereby pulmonary inflammation and hypersecretion. Given the reports on increased sputum NE concentrations upon rhDNase inhalation, there is a rationale for a combined rhDN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The primary targets for the liberated elastase are NET-associated histones and their subsequent enzymatic digest improves eDNA fragmentation [9]. However, the question remains whether the released active elastase should be controlled by addition of protease inhibitors [8,37] or whether alternative therapies that reduce the levels of NETosis should be devised.…”
Section: Discussionmentioning
confidence: 99%
“…The primary targets for the liberated elastase are NET-associated histones and their subsequent enzymatic digest improves eDNA fragmentation [9]. However, the question remains whether the released active elastase should be controlled by addition of protease inhibitors [8,37] or whether alternative therapies that reduce the levels of NETosis should be devised.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has been proposed that rhDNase can promote mixing of bacteria, antimicrobial agent and sputum [184] and improve gene transfer [185 -187] by improving penetration through sputum. It has been suggested that rhDNase may liberate cationic mediators such as neutrophil elastase bound to DNA in the airways [188,189] and hypertonic saline may potentiate neutrophilic inflammation. However, this hypothesis has not been confirmed in clinical studies [190 -192].…”
Section: Anti-inflammatory Treatment Strategiesmentioning
confidence: 99%
“…1 Recombinant human DNase (rhDNase) degrades highly viscosic DNA and was shown to be efficient in patients with cystic fibrosis (CF). 2,3 The use of rhDNase for the treatment of atelectasis in patients in the neonatal intensive care unit is a new concept, intended to liquefy the mucus when conventional therapies fail. 4 We present our experience with rhDNase use in a premature infant with recurrent atelectasis.…”
mentioning
confidence: 99%